2000
DOI: 10.1046/j.1365-2540.2000.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the European rabbit (Oryctolagus cuniculus) in the Iberian Peninsula inferred from RFLP analysis of the cytochrome b gene

Abstract: We studied mitochondrial DNA variation in the European rabbit through the examination of restriction fragment length polymorphism in 526 individuals from 20 locations spread across the Iberian Peninsula. Digestion with eight enzymes of a 1120-bp fragment comprising most of the cytochrome b gene resolved 38 dierent haplotypes. These haplotypes were distributed in two highly divergent clades, with dierent but overlapping geographical distributions, and with comparable levels of within-clade variation. The overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
166
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(179 citation statements)
references
References 28 publications
11
166
1
1
Order By: Relevance
“…The European rabbit comprises two distinct subspecies that are parapatrically distributed across the Iberian Peninsula: Oryctolagus cuniculus algirus, present in the southwest of Iberia, and Oryctolagus cuniculus cuniculus, which occurs in the northeast of Iberia (Biju-Duval et al, 1991;Branco et al, 2000). The two subspecies diverged in allopatry roughly 2 million years ago during the Quaternary glaciations (Biju-Duval et al, 1991;Geraldes et al, 2006) and have since come back into secondary contact, establishing a hybrid zone in central Iberia (Branco et al, 2002;Geraldes et al, 2005;Ferrand and Branco, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The European rabbit comprises two distinct subspecies that are parapatrically distributed across the Iberian Peninsula: Oryctolagus cuniculus algirus, present in the southwest of Iberia, and Oryctolagus cuniculus cuniculus, which occurs in the northeast of Iberia (Biju-Duval et al, 1991;Branco et al, 2000). The two subspecies diverged in allopatry roughly 2 million years ago during the Quaternary glaciations (Biju-Duval et al, 1991;Geraldes et al, 2006) and have since come back into secondary contact, establishing a hybrid zone in central Iberia (Branco et al, 2002;Geraldes et al, 2005;Ferrand and Branco, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Biju-Duval et al [1] first showed the occurrence of two highly divergent mtDNA lineages in Iberian wild rabbit populations by using RFLP of the whole molecule and tentatively dated their divergence at 1-2 million years ago. Later, Branco et al [2,3] described phylogeographical evidence for a recent contact zone bisecting the Iberian Peninsula from the Northwest to the Southeast and suggested that postglacial population expansions from two different refugia could explain the observed patterns. Recently, we reported high levels of nucleotide diversity in the rabbit SRY gene and suggested that this result could be explained by strong population subdivision [6].…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the incidence of cannibalism among the breeds of domestic rabbits have been described (Denenberg et al 1960). The genetic differences between the wild rabbit and the domestic breeds (Branco et al 2000) can partly explain the high incidence of cannibalism that we observed in wild cage-bred rabbits. These genetic differences predispose the animals to react differently to the handling and environment in captivity, resulting in a different incidence of cannibalism.…”
Section: Resultsmentioning
confidence: 83%